The influence of body mass index and age on C‐peptide at the diagnosis of type 1 diabetes in children who participated in the diabetes prevention trial‐type 1. Issue 3 (24th November 2017) - Sosenko, Jay M; Geyer, Susan; Skyler, Jay S; Rafkin, Lisa E; Ismail, Heba M; Libman, Ingrid M; Liu, Yuk‐Fun; DiMeglio, Linda A; Evans‐Molina, Carmella; Palmer, Jerry P
Abstract : Background/Objective: The extent of influence of BMI and age on C‐peptide at the diagnosis of type 1 diabetes (T1D) is unknown. We thus studied the impact of body mass index Z‐scores (BMIZ) and age on C‐peptide measures at and soon after the diagnosis of T1D. Methods: Data from Diabetes Prevention Trial‐Type 1 (DPT‐1) participants <18.0 years at diagnosis was analyzed. Analyses examined associations of C‐peptide measures with BMIZ and age in 2 cohorts: oral glucose tolerance tests (OGTTs) at diagnosis ( n = 99) and mixed meal tolerance tests (MMTTs) <6 months after diagnosis ( n = 80). Multivariable linear regression was utilized. Results: Fasting and area under the curve (AUC) C‐peptide from OGTTs ( n = 99) at diagnosis and MMTTs ( n = 80) after diagnosis were positively associated with BMIZ and age ( P < .001 for all). Associations persisted when BMIZ and age were included as independent variables in regression models ( P < .001 for all). BMIZ and age explained 31%‐47% of the variance of C‐peptide measures. In an example, 2 individuals with identical AUC C‐peptide values had an approximate 5‐fold difference in values after adjustments for BMIZ and age. The association between fasting glucose and C‐peptide decreased markedly when fasting C‐peptide values were adjusted ( r = 0.30, P < .01 to r = 0.07, n.s.). Conclusions: C‐peptide measures are strongly and independently related to BMIZ and age at and soon after the diagnosis of T1D. Adjustments for BMIZ and age cause substantial changes in C‐peptide values, and impact the association between glycemia and C‐peptide. Such adjustments can improve assessments of β‐cell impairment at diagnosis.